Developing Website English Learning Application with Google Site to Enhance Grammar Understanding - Ardiel, Vonny; Sri Mulyani Rusli (Edelweiss : Journal Of Innovation In Educational Research, 2024)
Grammar understanding is the main point to get the English skill. This study explores the development of a website-based English learning application aimed at enhancing grammar understanding, utilizing Google Sites as the platform. The application was developed following the System Development Life Cycle (SDLC) - Waterfall Model, encompassing phases of requirements analysis, system design, implementation, testing, and deployment. The primary objective was to create an accessible, user-friendly platform that provides comprehensive grammar tutorials, interactive exercises, and quizzes to reinforce learning. During the development process, key user needs were identified, leading to the design of a structured and responsive website. The implementation phase focused on integrating multimedia content and interactive elements to engage learners and facilitate effective grammar practice. Testing involved both functionality and user experience assessments, with feedback indicating that the application successfully supported grammar learning, though some improvements were recommended for clarity and content breadth. The study concludes that using Google Sites for educational purposes offers a practical solution for creating accessible learning tools. The application demonstrated significant potential in enhancing grammar understanding among users, with future improvements suggested to expand the range of topics and interactive features. This project provides a foundation for further exploration of web-based language learning applications using low-cost, widely available platforms.